High prevalence of rare ryanodine receptor type 1 variants in patients suffering from aneurysmatic subarachnoid hemorrhage: A pilot study. (November 2017) - Coburger, Jan; Kapapa, Thomas; Wirtz, Cristian Rainer; Jurkat-Rott, Karin; Klingler, Werner
Highlights: RYR 1 Ca2+ receptor is highly relevant for genesis of vasospasm and bleeding disorders. First prospective pilot-study on prevalence of RYR 1 receptor variants in SAH patients. First assessment of pathogenetic changes in the resulting RYR 1 protein. High prevalence of RYR 1 variants in SAH patients compared to the general population. Potential high value for further research and the understanding of SAH. Abstract: Subarachnoid hemorrhage (SAH) remains a challenging neurosurgical disease. The ryanodine receptor type 1 Ca2+ channel (RyR1) plays a crucial role in vasoconstriction and hemostasis. Mutations of the encoding gene, RYR1, are known to cause susceptibility to malignant hyperthermia (MH). Recently, a RYR1 mutation was found to be associated with abnormal bleeding times. Therefore, an assessment of the RYR1 gene might be of high relevance in patients with aneurysmatic SAH. In the presented pilot study, we screened 10 patients suffering from SAH for RYR1 variants and, for the first time in SAH, performed an assessment of pathogenicity of these variants using protein prediction software. Four of the patients showed a RYR1 variant. For three of the variants, p.Glu79Lys, p.Arg885C, p.Glu2635 Val, all three programs predicted pathogenicity. Their prevalence in the general population is very low i.e. under 0.005%. For the fourth variant, p.Pro4501Leu (RS73933023), the results of the prediction programs were discrepant and the prevalence in the general population was high, i.e. almost 0.5%, which is too frequent to be associated with the rare SAH phenotype. Clinical evaluation revealed that no differences concerning neurological outcome, presence of vasospasm, ischemic deficits and mean hospital stay between patients with and without variants were found. However, in our series SAH patients have an increased frequency of rare RYR1 variants. Hence, potentially contributing to the pathogenesis of SAH. Further data is needed to confirm this preliminary result.